The characteristics of psychosocial risks in the banking sector: A brief report - Aleksander Stańczak; Dorota Merecz-Kot (Nofer Institute of Occupational Medicine, 2014)
Background: Psychosocial risks in workplace are common phenomenon, stressing even for so-called white collar workers. The aim of the study was to indicate the most important threats in terms of banking sector employees. Material and Methods: The studied subjects were 484 employees employed in 26 companies. The Scale of Psychosocial Risk (SPR) was used as a research tool. Results: The most frequent and the most stressful categories of threats were: lack of control over workload and lack of careerdevelopment chances. Banking sector employees are obliged to follow strict procedures of customer service and they regard theirpromotion chances as low. Employees's appraisal system is another strongly stressful factor. Work in a banking sector involvesa great mental strain and the high risk of dismissal. Interpersonal relationships at work turned out to be the least stressful workfacet in the banking sector. Conclusions: Given the most serious sources of psychosocial risks, the authors suggested to take thefollowing actions: changes in work and work control system, education of employees and managerial staff and regular monitoring of occurring threats. Med Pr 2014;65(3):399-405